A Study on PHERB Powertrain Modeling and Analysis - J. S. Norbakyah; A. R. Salisa (International Journal of Electrical and Computer Engineering (IJECE), 2018)
A study on plug-in hybrid electric recreational boat (PHERB) powertrain with a special energy management strategy modeling and analysis was presented in this paper. Firstly, the boat components are sized to meet the expected power and energy requirements through a power flow analysis. Then, the model is tested numerically in the MATLAB/SIMULINK environment using the existing driving cycle. The accuracy of the model is verified by a comparison of the component between the simulation results from PHERB and advanced vehicle simulator (ADVISOR) software. The simulation results of component, fuel economy and emission of PHERB and hybrid electric vehicle models in ADVISOR are compared.